Heritage language policies of the Iranian diaspora in New Zealand. Issue 4 (1st October 2020) - Gharibi, Khadij; Seals, Corinne
ABSTRACT: The present study investigates immigrant parents' family language policies in regards to their children's heritage language development and maintenance by utilizing Spolsky's theoretical model on which research on family language policy (FLP) considerably draw. Following the three core components of the FLP model, Iranian parents' beliefs, practices and efforts in relation to their children's home language (i.e. Persian/Farsi) acquisition and maintenance are investigated. The data were collected through semi-structured interviews with twenty-five parents of Persian-English bilinguals (6–18 year old) in New Zealand. The findings reveal that although the parents hold positive beliefs towards the family language acquisition and maintenance, there are discrepancies between their language ideologies and family language practices. In light of these inconsistencies between parents' beliefs and their actual family language practices and efforts to preserve the heritage language, we argue that to raise their children bilingually, immigrant parents should not only have strong beliefs towards family language acquisition and maintenance, but also their everyday practices and efforts should be in line with their beliefs.